Genome‐wide population affinities and signatures of adaptation in hydruntines, sussemiones and Asian wild asses - Jianfei Pan; Xuexue Liu; Mateusz Baca; Laure Calvière‐Tonasso; Stéphanie Schiavinato; Loreleï Chauvey; Gaétan Tressières; Aude Perdereau; Jean‐Marc Aury; Pedro H. Oliveira; Patrick Wincker; Aida Abdykanova; et al. (Molecular Ecology, 2024)
The extremely rich palaeontological record of the horse family, also known as equids, has provided many examples of macroevolutionary change over the last ~55 Mya. This family is also one of the most documented at the palaeogenomic level, with hundreds of ancient genomes sequenced. While these data have advanced understanding of the domestication history of horses and donkeys, the palaeogenomic record of other equids remains limited. In this study, we have generated genome‐wide data for 25 ancient equid specimens spanning over 44 Ky and spread across Anatolia, the Caucasus, Central Asia and Mongolia. Our dataset includes the genomes from two extinct species, the European wild ass, Equus hydruntinus , and the sussemione Equus ovodovi . We document, for the first time, the presence of sussemiones in Mongolia and their survival around ~3.9 Kya, a finding that should be considered when discussing the timing of the first arrival of the domestic horse in the region. We also identify strong spatial differentiation within the historical ecological range of Asian wild asses, Equus hemionus , and incomplete reproductive isolation in several groups yet considered as different species. Finally, we find common selection signatures at ANTXR2 gene in European, Asian and African wild asses. This locus, which encodes a receptor for bacterial toxins, shows no selection signal in E. ovodovi , but a 5.4‐kb deletion within intron 7. Whether such genetic modifications played any role in the sussemione extinction remains unknown.